(untitled) (Research, Society and Development, 2020)
This research had as its object of study the organization of teaching in educational districts, delimiting the field of research to a case study carried out in the municipality of Quixadá, Ceará. The general objective of the research was to analyze the grouping of schools in the municipal education network in educational districts, as well as to discuss centralized management and the multiple functions performed by educational directors and coordinators. The study is organized in three stages: the first stage discusses the organization of education in Brazil, the state’s duty regarding the provision of basic education. The second moment presents the types and theoretical conceptions about school management and educational management. The third and last moment deals with field research carried out through participant observation and documentary analysis, which allowed to describe, explain and analyze the organization and management of teaching in educational districts. This work made it possible to know and reflect on the organization and management of schools in the municipal school system that reverberates in the learning and school permanence of elementary school students. Management in educational districts limits the participation of school actors in school-related decision-making, in addition to interfering with administrative and pedagogical autonomy guaranteed by law. In conclusion, management in educational districts is incompatible with the principles of democratic and participatory management.